The influence of transition and heavy metal ions on ATP-ases activity in rat synaptic plasma membranes - VESNA VASIC; KATARINA KRINULOVIC; DANIJELA KRSTI; LJUBICA VUJISIC (Journal of the Serbian Chemical Society, 2004)
The influence of transition metal (Cu2+, Zn2+, Fe2+ and Co2+) and heavy metal ions (Hg2+, Pb2+ and Cd2+) on the activities of Na+/K+-ATPase and Mg2+-ATPase isolated from rat synaptic plasma membranes (SPM) was investigated. The aim of the study was to elucidate the inhibition of both ATPase activities by exposure to the considered metal ions as a function of their affinity to bind to the SH containing ligand L-cysteine, as a model system. The half-maximum inhibitory activities (IC50) of the enzymes were determined as parameters of rectangular hyperbolas and correlated with the stability constant (Ks) of the respective metal-ion-L-cysteine complex. The linear Dixon plots indicate equilibrium binding of the investigated ions to both enzymes.